University students vary their use of textese in digital messages to suit the recipient. (29th March 2016) - Kemp, Nenagh; Clayton, Jennifer
Abstract : Background: The casual, abbreviated writing style sometimes known as 'textese' (e.g., sorry im late ☹) has become widespread with the rise of digital communication. We explored Australian university students' views on, and use of, textese across three modalities (text message, Facebook post, email) and three recipient types (friends, peers, lecturers). Methods: In Study 1, 51 undergraduates composed messages across the three modalities to the three recipient types. They also rated the appropriateness of messages written with high, medium and no textese, across modality and recipient types. In Study 2, 37 additional students provided examples of their own sent messages across modalities and recipients. Results: Overall, participants rated textese use as more appropriate, and used significantly more textese, in messages to friends, than to peers, than to lecturers. Conclusions: Undergraduates are sensitive to when and where it is appropriate to use textese and vary their use (and opinions) of written language as a function of the recipient.